The Effectiveness of the Learning Module Cooperative Learning Student Facilitator and Explaining - Rahmatullah, Ramadhani; Syahril, Syahril; Abdullah, Rijal (Universitas Pendidikan Ganesha, 2021)
Low understanding of students impacts low student learning outcomes in subjects due to teacher-centered learning orientation. Students have not been able to learn independently and only rely on material explanations from the teacher. Available teaching materials have not been able to facilitate students to learn independently and thoroughly. This research aims to analyze the effectiveness of the cooperative learning module student facilitator and explain. The research used to research and development methods using the Four-D (4D) development model. The data collection methods used were questionnaires and tests. The method of analysis was carried out by descriptive and inferential analysis with the t-test. The results obtained from this study were the validity of the module based on cooperative type student facilitator, and explaining was declared valid on the material aspects in the module with a total validity score was 99.3%, and the module format aspect was declared valid with a total score of 91.7. The student facilitator type of cooperative learning module is practically based on the teacher's assessment with a practical score of 88.62% in the very practical category and 88.98% in the very practical category. The module effectiveness score increases the pretest score of 55.00 to 84.58 in the post-test score with the gain score in the medium category. Based on the findings of this study, it is concluded that the module based on cooperative type student facilitator and explaining is valid, practical, and effective to be used as a learning medium in the subject of estimating construction costs